Interfacial crack growth in piezoelectric-piezomagnetic bi-layered structures with a modified mechanical energy release rate criterion. (15th April 2021) - Yan, Z.; Feng, W.J.; Zhang, Ch.
Highlights: Growth path simulation of interfacial cracks in magnetoelectric composite structures. Choice of enrichment functions depend on different singular properties of crack tips. Fracture criterion is modified and extended to magnetoelectric composite structures. The relation of fracture toughness and poling direction are considered. Abstract: This paper investigates the interfacial crack growth in the piezoelectric-piezomagnetic (PE-PM) bi-layered composite structures under quasi-static assumption. The extended finite element method (X-FEM) is utilized to solve the fracture parameters and simulate the growth paths, in which the suitable enrichment functions are chosen according to different singular properties of the crack tip. Based on the crack-tip fields of interfacial crack in PE-PM bimaterials, the mechanical energy release rate (MERR) criterion is modified and extended to the PE-PM composites where the relation of fracture toughness and poling direction should be considered. In the numerical examples, the validity of the present scheme is firstly verified by compared with the three point bending test for PE material. And then, with the modified MERR criterion, the effects of the geometries of cracked model, electro-magneto-mechanical coupling loadings and fracture toughness on interfacial crack growth are emphatically studied.